2013
DOI: 10.1155/2013/519387
|View full text |Cite
|
Sign up to set email alerts
|

Greater Skeletal Gains in Ovary Intact Rats at Maturity Are Achieved by Supplementing a Standardized Extract ofButea monospermaStem Bark that Confers Better Bone Conserving Effect following Ovariectomy and Concurrent Treatment Withdrawal

Abstract: With a longitudinally designed study, we tested whether an acetone soluble fraction (ASF) from the stem bark of Butea monosperma resulted in maximizing bone gain in rats during growth and maturation and thus protected against osteopenia following ovariectomy (OVx) with concomitant treatment withdrawal. Female rats at weaning were given ASF (100 mg/kg/d) or vehicle for 12 weeks, and baseline skeletal parameters (micro-CT) and total plasma antioxidant status (TAS) were measured. At this stage, one group was OVx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…For BMD calibration, 2-mm-diameter hydroxyapatite phantom rods with known BMD (0.25 and 0.75 g/cm 3 ) were used. For each analysis, the estimated BMD was determined based on linear correlation between the mCT attenuation coefficient and BMD (28).…”
Section: Microcomputed Tomographymentioning
confidence: 99%
“…For BMD calibration, 2-mm-diameter hydroxyapatite phantom rods with known BMD (0.25 and 0.75 g/cm 3 ) were used. For each analysis, the estimated BMD was determined based on linear correlation between the mCT attenuation coefficient and BMD (28).…”
Section: Microcomputed Tomographymentioning
confidence: 99%
“…Volumetric BMD (vBMD) was determined from the volume of intrest (VOI) using μCT scans. Hydroxyapatite (HA) phantom rods of 8 mm diameter with known BMD (0.25 g/cm 3 and 0.75 g/cm 3 ) were employed for calibration as described …”
Section: Methodsmentioning
confidence: 99%
“…Hydroxyapatite (HA) phantom rods of 8 mm diameter with known BMD (0.25 g/cm 3 and 0.75 g/cm 3 ) were employed for calibration as described. (29,30)…”
Section: Micro-computed Tomographymentioning
confidence: 99%
“…μCT scanning and analysis of excised bones were carried out using the SkyScan 1076 μCT scanner (Aartselaar, Belgium) as reported previously (Khedgikar et al ., ; Sharan et al ., ; Khan et al ., ). Serum antioxidant level was measured according to the manufacturer's protocol using antioxidant measurement kit as reported earlier (Srivastava et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Simple isoflavones such as daidzein and genistein harbour antimicrobial activity and are also precursor of complex isoflavonoids, phytoalexins (Samac and Graham, ). In addition to benefits to plant itself, these molecules have been shown to improve human health through protecting against hormone‐dependent cancers, cardiovascular disease, osteoporosis and menopausal symptoms (Cornwell et al ., ; Dixon, ; Srivastava et al ., ,b; Tyagi et al ., ; Pandey et al ., ; Trivedi et al ., ). Based on the in vitr o, in vivo and epidemiological studies, isoflavonoids have been reported to exhibit antioxidant, antimutagenic, anticarcinogenic, anti‐osteoporotic and antiproliferative activities in human and animal systems (Birt et al ., ; Iwasaki et al ., ; Miadokova et al ., ; Miadokova, ; Ryan‐Borchers et al ., ; Scarpato et al ., ).…”
Section: Introductionmentioning
confidence: 99%